The experience of social inclusion for people with intellectual disability within community recreational programs: A systematic review. Issue 4 (2nd October 2018) - Merrells, Jessica; Buchanan, Angus; Waters, Rebecca
ABSTRACT: Background: Social inclusion is a vital domain in quality of life and is enhanced through recreational programs. People with intellectual disability have been provided with fewer opportunities to participate in these groups, thus hindering social inclusion. Method: Five databases (CINAHL, Ovid, ProQuest, ScienceDirect, and Wiley Online Library) were electronically searched and narrowed using inclusion/exclusion criteria. The methodological quality was assessed using standard quality assessment criteria. Results: Out of 135 retrieved results, 12 articles were included. Data were predominantly collected using questionnaires, scales, and interviews. Ages of the people with intellectual disability ranged from 5 to 65 years, and the sample size ranged from 30 to 2, 556 persons. Four key themes became apparent in the literature: (1) the impact of physical and social independence, (2) the amount of social interaction and participation, (3) the impact of culture and attitudes, and (4) the outcomes of social inclusion. Conclusions: Social inclusion and participation in leisure activities for people with intellectual disability increase with greater functional independence and positive community attitudes. This participation results in positive outcomes. People with an intellectual disability participate less in recreational programs. Further research is needed regarding the experience from the person's point of view.